Enzymolytic soybean meal improves growth performance, economic efficiency and organ development associated with cecal fermentation and microbiota in broilers offered low crude protein diets - Zhu, Xin; Gao, Kai; Qi, Yongqiang; Yang, Guiqin; Liu, Haiying (Frontiers in Veterinary Science, 2023)
The objective of this experiment was to determine the effect of low crude protein (CP) diets containing increasing amounts of enzymolytic soybean meal (ESBM) on growth performance, economic benefit and organ development and the role of cecal fermentation and microbiota in broilers. A total of 360 one-day-old Arbor Acres chicks were randomly allocated into 6 groups with 6 replicates and 10 chicks each. The six dietary treatments consisted of a standard high-CP diet (PC), a low-CP diet (NC), and an NC diet with 0.5%, 1.0%, 1.5%, or 2.0% ESBM. The experiment lasted for 42 days. Compared to PC, NC showed decreased (P < 0.05) average daily gain (ADG) in broilers from 22 to 42 days and from 1 to 42 days, while increasing levels of ESBM quadratically increased (P < 0.05) ADG from 1 to 42 days. Feed cost and total revenue in the NC were lower (P < 0.05) than that in the PC, while supplementation with ESBM in the NC linearly increased (P < 0.05) net profit and economic efficiency in broilers. There were significant differences (P < 0.05) in the liver, proventriculus and gizzard indices between the PC and NC groups, and supplementation with ESBM linearly increased (P < 0.05) the relative weights of liver, pancreas, proventriculus and gizzard in broilers at 42 days of age. The PC group had a higher cecal acetic acid concentration at 21 days and propionic acid concentration at both 21 and 42 days than the NC group (P < 0.05). Cecal acetic acid and propionic acid concentrations linearly increased (P < 0.05) with increasing levels of ESBM in broilers at 42 days of age. No significant differences in ACE, Chao1, Shannon and Simpson indices were observed among groups (P > 0.05), while the cecal abundances of Bacteroides, Faecalibacterium and Clostridium IV increased (P < 0.05) with the increasing level of ESBM in the low-CP diets. In conclusion, feeding ESBM improved economic efficiency, digestive organ development, cecal fermentation and microbial community composition, and up to 2.0% ESBM addition had no negative effect on the growth performance in broilers fed low CP diets.